GARCH option pricing with volatility derivatives - Oh, Dong Hwan; Park, Yang-Ho (Journal of Banking & Finance, 2023)
This paper studies benefits of joint estimations for GARCH option pricing that utilize both stock returns and volatility derivatives. The proposed estimations not only provide realistic volatility term structures but also generate flat skewness term structures much like those seen in the S&P 500 index (SPX) options data. In particular, the estimated GARCH models yield a highly persistent volatility component, which allows the leverage effect to hold up until long horizons. Such a persistent volatility component is key to modeling long-term tail risk and pricing long-term put options. Overall, our exercise highlights the usefulness of volatility derivatives in GARCH option valuation.